A Study on the Bases of Space of Vector Valued Entire Multiple Dirichlet Series - Hussein, Mushtaq; Nagem, Nagem (Iraqi Journal of Science, 2024)
Let  , 1( )1 2 ,( , ) 1 2m ns sm nf s s a e m n   , (s   it , j 1,2) j j j  ,  m 1  and n 1  being an increasing sequences of positive numbers and a E m n  , where Eis Banach algebra, represent a vector valued entire Dirichlet functions in twovariables. The space  of all such entire functions having order at most equal to is considered in this paper. A metric topology using the growth parameters of f isdefined on  and its various properties are obtained. The form of linear operator onthe space  is characterized and proper bases are also characterized in terms ofgrowth parameters  .